Core-shell structure oxide solid electrolyte powder as well as preparation method and application thereof
Through the preparation method of core-shell structure oxide solid electrolyte powder, the grain boundary defects and insulating layer generation problems of garnet oxide electrolyte are solved, and the chemical stability and electrical properties of the electrolyte are improved through the boron lithiate protective layer, which is improved. Overall performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411255533.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-10
AI Technical Summary
The existing garnet oxide solid electrolytes have grain boundary defects and insulating layer generation during the synthesis process, which makes it difficult to improve performance and is sensitive to water and carbon dioxide, affecting the chemical stability and electrical properties of the battery.
Using the preparation method of core-shell structure oxide solid electrolyte powder, fine and uniform oxide electrolyte particles are formed through the first pressurized homogenization and crushing steps and the second pressurized homogenization and crushing steps, and the surface is coated with boron lithiate protection. layer to prevent chemical reactions and lithium ions loss, improve chemical stability and electrical properties.
The grain boundary defect structure is optimized, the chemical stability and battery performance of the electrolyte are enhanced, the insulating layer is prevented, and the electrical performance and cycle life of lithium-ion batteries are significantly improved.
Smart Images

Figure CN119297378A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a core-shell structure oxide solid electrolyte powder and a preparation method and application thereof. Background Art
[0002] Energy is an important material basis for the survival and development of human society. Lithium-ion batteries are one of the most promising new energy storage technologies, and lithium electrolytes are an important component of lithium-ion batteries. Electrolytes are generally lithium salts, such as lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide) and other lithium salts dissolved in carbonate solvents or ether solvents to form organic liquid electrolytes. However, metallic lithium is highly reactive to organic electrolyte lithium salts and is easily corroded, causing the depletion of organic lithium salts, resulting in poor stability of the negative electrode interface, increased battery resistance, reduced battery coulomb efficiency, shortened cycle life, potential safety hazards, and flammable and explosive properties.
[0003] Solid electrolytes with high safety factors and high energy density have attracted widespread attention. At present, the main inorganic solid electrolytes include perovskite, NASICON, garnet and sulfide materials. In the perovskite structure solid electrolyte, during the cycle of lithium metal batteries, tetravalent Ti will be reduced to trivalent Ti, causing the loss of Li and La and the deformation of Ti-O polyhedron, which in turn causes the unstable crystal structure of the material. NASICON-type materials are considered suitable for high-voltage solid electrolyte batteries, but they are unstable to lithium metal and difficult to use in lithium metal batteries. The chemical stability of sulfide systems is generally poor, and the material is very sensitive to moisture, reacting with water to produce gaseous hydrogen sulfide. Garnet-type oxide solid electrolytes have broad application prospects due to their high ionic conductivity and good chemical stability.
[0004] However, the mainstream synthesis methods of garnet-type oxide solid electrolytes include hot solid-phase sintering, sol-gel, and co-precipitation. The defects that appear in the synthesis process will lead to high grain boundary impedance, including internal grain boundary resistance, the interface layer between the electrolyte and the electrode, and the insulating layer generated by the reaction of garnet-type oxide solid electrolyte with water and carbon dioxide in the air, making it difficult to improve its performance. Summary of the invention
[0005] A technical problem to be solved by the present invention is how to provide a core-shell structured oxide solid electrolyte powder and a preparation method and application thereof, so that the grain boundary defect structure of the core-shell structured oxide solid electrolyte powder is optimized, and at the same time, by adjusting the surface composition of the electrolyte, its chemical stability is improved, and the formation of an insulating layer can be prevented, thereby improving the performance of the battery.
[0006] In order to solve the above technical problems, an embodiment of the present invention provides a method for preparing a core-shell structured oxide solid electrolyte powder, which comprises the following steps:
[0007] 1) preparing an electrolyte raw material into a first suspension;
[0008] 2) subjecting the first suspension to a first pressurized homogenization and crushing process to obtain a second suspension;
[0009] 3) adding lithium salt to the second suspension to perform a second pressurized homogenization and crushing to obtain a third suspension;
[0010] 4) The third suspension is filtered, dried, and sintered in an inert or neutral atmosphere to obtain a core-shell structured oxide solid electrolyte powder.
[0011] In some embodiments, the particle size of the electrolyte raw material is 0.1-500 μm.
[0012] In some embodiments, the flow rate of the first pressurized homogenization crushing and the second pressurized homogenization crushing is 500-2000 m / s, and the pressure is 1000-1500 bar; the temperature of the second suspension and the third suspension is ≤120°C, and the viscosity is ≤2000cp.
[0013] In some embodiments, the lithium salt is a boron lithium compound selected from at least one of LiBH4, LiBF4, Li2B4O7, Li3BO3 and LiBO2; based on the mass of the electrolyte raw material, the addition amount of the lithium salt is 0.1 to 15%.
[0014] In some embodiments, after the step of adding lithium salt to the second suspension for second pressurized homogenization and crushing, the step also includes: adding lithium salt to the suspension after the second pressurized homogenization and crushing, and performing the second pressurized homogenization and crushing again; the step of adding lithium salt to the suspension after the second pressurized homogenization and crushing, and performing the second pressurized homogenization and crushing again is performed n times, where n is a natural number.
[0015] In some embodiments, the step of preparing the electrolyte raw material into a first suspension is as follows:
[0016] 1a) dissolving a soluble salt in a first solvent to obtain a salt solution; the soluble salt is selected from at least one of nitrates, sulfates, halides, hydroxides and carbonates; the first solvent is selected from any one of water, acetonitrile, anhydrous ethanol, methanol, tetrahydrofuran, dimethylformamide and dimethyl sulfoxide;
[0017] 1b) adding ammonia water dropwise to the salt solution to form a precipitate; the mass concentration of the ammonia water is 0.01-10%;
[0018] 1c) filtering the precipitate, adding a second solvent thereto, stirring, and obtaining a first suspension; the second solvent is selected from any one of water, anhydrous ethanol, methanol and dimethylformamide.
[0019] In some embodiments, the sintering temperature is 200-500° C., the sintering time is 0.5-5 h, and the sintering atmosphere is air, nitrogen, argon or helium.
[0020] In some embodiments, the sintering is cold isostatic pressing sintering or hot isostatic pressing sintering; or, the sintering further includes a second sintering; the temperature of the second sintering is 800-1050°C.
[0021] In order to solve the above technical problems, an embodiment of the present invention further provides a core-shell structured oxide solid electrolyte powder, wherein the particles constituting the core-shell structured oxide solid electrolyte powder include:
[0022] The core is a solid particle made of an oxide electrolyte;
[0023] The shell layer is coated on the surface of the solid particles; the material of the shell layer is boron lithium compound.
[0024] In order to solve the above technical problems, an embodiment of the present invention further provides an application of the aforementioned core-shell structure oxide solid electrolyte powder in the field of lithium electronic battery technology.
[0025] The core-shell structure oxide solid electrolyte powder provided by the present invention and its preparation method and application, firstly, a first suspension prepared with oxide electrolyte raw materials is subjected to a first pressurized homogenization and crushing, so that the raw materials are fully homogenized and refined, so that the particle size of the raw material powder is finer and more uniform, so that the powder density after later sintering is better, and the interface resistance caused by defective grain boundaries inside the solid electrolyte can also be improved; secondly, the present invention adds lithium salt to the raw material powder subjected to the first pressurized homogenization and crushing, and then subjects the mixture of the two to a second pressurized homogenization and crushing, so that the lithium salt compound is coated on the surface of the oxide electrolyte raw material powder to form a protective layer; the formed protective layer can, on the one hand, prevent the lithium-containing oxide in the oxide electrolyte from chemically reacting with water and carbon dioxide in the air to produce an insulating layer to cause grain boundary impedance, thereby improving the stability of the oxide electrolyte, and on the other hand, the protective layer can also prevent the loss of lithium ions in the oxide electrolyte during the later sintering process, thereby improving its electrical properties.
[0026] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the particle structure of the core-shell structure oxide solid electrolyte powder of the present invention;
[0028] Figure 2 This is a schematic diagram of the structure of the present invention using a homogenizer for pressurized homogenization and crushing. DETAILED DESCRIPTION
[0029] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following, in combination with the accompanying drawings and preferred embodiments, describes in detail a core-shell structure oxide solid electrolyte powder and its preparation method and application proposed by the present invention, its specific implementation method, structure, characteristics and effects.
[0030] The present invention provides a method for preparing a core-shell structured oxide solid electrolyte powder, which comprises the following steps:
[0031] First, the oxide electrolyte raw materials are prepared into a first suspension.
[0032] The oxide electrolyte raw material can be directly used to prepare the first suspension using oxide electrolyte raw materials purchased from the market. This operation step can be carried out using the suspension / solution preparation method commonly used in the art, and is not specifically limited in the present invention. The powder particle size of the oxide electrolyte raw material is controlled to be 0.1 to 500 μm.
[0033] In order to make the metal distribution in the oxide electrolyte powder more uniform and to make it have better diffusion performance during subsequent sintering, the present invention preferably prepares the oxide electrolyte raw materials by coprecipitation method. The specific operation is as follows:
[0034] The first step is to dissolve a soluble salt containing the corresponding metal in a first solvent to obtain a salt solution. The soluble salt containing the corresponding metal can be selected according to the chemical formula of the inorganic oxide electrolyte to be obtained.
[0035] The first solvent is selected from any one of water, acetonitrile, anhydrous ethanol, methanol, tetrahydrofuran, dimethylformamide and dimethyl sulfoxide.
[0036] The inorganic oxide electrolyte is mostly used in perovskite type, LISICON type, NASICON type and garnet type, which are not specifically limited in the present invention. The soluble salt containing the corresponding metal is selected from at least one of nitrate, sulfate, halide, hydroxide and carbonate. When the inorganic oxide electrolyte is garnet type LLZO, the lithium salt that can be used is selected from any one of lithium nitrate, lithium carbonate, lithium fluoride, lithium chloride, lithium bromide and lithium iodide, the lanthanum salt is selected from lanthanum nitrate, and the zirconium salt is selected from any one of zirconium nitrate, zirconium bromide, zirconium chloride, zirconium fluoride and ZrOCl2.
[0037] The second step is to drop ammonia water into the salt solution, and the ammonia water produces hydroxide ions, which can combine with metal ions to form precipitation. The concentration of ammonia water should not be too low, otherwise it may cause the neutralization speed to be too slow and affect the production efficiency; and the concentration of ammonia water should not be too high, otherwise it may be difficult to control due to the excessively fast neutralization speed, and the high concentration of ammonia water also has higher volatility; the preferred mass concentration of the ammonia water in the present invention is 0.01-10%.
[0038] The third step is to filter the precipitate, then add a second solvent to the filtered solid component, and stir it with magnetic force to obtain a first suspension. The second solvent is selected from any one of water, anhydrous ethanol, methanol and dimethylformamide.
[0039] Next, the prepared first suspension is subjected to a first pressurized homogenization crushing to obtain a second suspension. The pressurized homogenization crushing of the present invention is carried out by a homogenizer. The structural schematic diagram of the pressurized homogenization crushing by a homogenizer is shown in the attached figure. Figure 2 As shown in the figure, 1 represents the raw material fluid, 2 represents the equipment base, 3 represents the collision cup, 4 represents the fluid after crushing, 5 represents the collision valve, and the arrow represents the flow direction of the fluid; compared with the conventional method of using ball mill to refine the powder, the use of a homogenizer to refine the powder has a higher crushing energy; the homogenizing valve is the core component of the homogenizer, which is homogenized at a high flow rate and high pressure, and the cavitation of the material can be caused by the impact. The impact and shearing effect can achieve a finer and more uniform particle size of the oxide electrolyte raw material powder. The preferred flow rate of the pressurized homogenization crushing of the present invention is 500-2000m / s and the pressure is 1000-1500bar.
[0040] Then, lithium salt is added to the second suspension to perform a second pressurized homogenization and crushing to obtain a third suspension.
[0041] In the present invention, the pressurized homogenization and crushing of the oxide electrolyte raw material (first pressurized homogenization and crushing) and the pressurized homogenization and crushing after adding the lithium salt (second pressurized homogenization and crushing) are carried out separately. The reason is that the technical purpose of the first pressurized homogenization and crushing is to control the particle size of the oxide electrolyte to be finer and more uniform; the technical purpose of the second pressurized homogenization and crushing is to coat the lithium salt; if the first pressurized homogenization and crushing are combined with the second pressurized homogenization and crushing, the lithium salt cannot be completely coated on the surface of the oxide electrolyte particles, thereby affecting the improvement effect of the lithium salt on the electrical properties of the oxide electrolyte.
[0042] The present invention preferably uses a lithium salt as the coating layer on the surface of the oxide electrolyte; further preferably uses a boron lithium compound as the coating layer on the surface of the oxide electrolyte; the reason for this technical design is that the role of the electrolyte is to achieve the migration of positive ions between the two electrodes; although sodium ions also have a relatively good mobility, it is difficult to determine whether lithium-sodium-lithium migration can be achieved and whether the migration energy barrier is too high, and it is difficult to prove that the migration channel suitable for lithium ions inside the microstructure is suitable for the migration of sodium ions. In order to ensure the migration of positive ions between the two electrodes, the present invention preferably forms a lithium ion migration channel with "lithium in the oxide electrolyte-lithium in the coating layer-lithium in the oxide electrolyte", so that there is neither an ion migration energy barrier nor the problem of migration channel adaptability.
[0043] The boron lithium compound of the present invention is preferably at least one of LiBH4, LiBF4, Li2B4O7, Li3BO3 and LiBO2, but the lithium salt is not limited to the aforementioned preferred range. The technical purpose of adding the boron lithium compound to the oxide electrolyte powder is to completely cover the particle surface of the oxide electrolyte powder, so its addition amount should not be too small. The present invention preferably adds ≥0.1% of the lithium salt; considering the cost performance, on the basis of being able to completely cover the particle surface of the oxide electrolyte powder and being able to complete ion migration well, the content of the lithium salt should not be too high. The present invention preferably adds ≤15% of the lithium salt; the aforementioned addition amount is the mass percentage based on the mass of the oxide electrolyte raw material.
[0044] The device for the second pressurized homogenization and crushing of the present invention is a homogenizer, and the control of its flow rate and pressure, as well as the temperature and viscosity of the suspension are the same as those of the first pressurized homogenization and crushing, and will not be repeated here.
[0045] In order to improve the improvement effect of the coating layer lithium salt on the electrical properties of the oxide electrolyte, obtain better surface lithium ion mobility and the effect of replenishing lithium ion loss, the present invention preferably performs the lithium salt coating multiple times, and obtains a multilayer oxide electrolyte powder by multiple coatings. The steps of multiple coatings are as follows: adding lithium salt to the suspension after the second pressurized homogenized crushing, and performing the second pressurized homogenized crushing again; adding lithium salt to the suspension after the second pressurized homogenized crushing, and performing the second pressurized homogenized crushing again are performed n times, where n is a natural number.
[0046] Finally, the third suspension is filtered, dried, and sintered in an inert or neutral atmosphere to obtain a core-shell structured oxide solid electrolyte powder.
[0047] The sintering can adopt the sintering process parameters commonly used in the co-precipitation lithium ion electrolyte sintering; the present invention preferably has a sintering temperature of 200-500°C, a sintering time of 0.5-5h, and a sintering atmosphere of air, nitrogen, argon or helium.
[0048] In order to further improve the density of the finished oxide electrolyte product, the sintering is cold isostatic pressing sintering or hot isostatic pressing sintering; or, the sintering further includes a second sintering; the temperature of the second sintering is 800-1050°C.
[0049] The present invention also provides a core-shell structure oxide solid electrolyte powder, as shown in the attached Figure 1 As shown, the particles constituting the core-shell structured oxide solid electrolyte powder include:
[0050] The core 12 is the central part of the particle, and its material is a solid particle of oxide electrolyte;
[0051] The shell layer 11 is coated on the surface of the solid particles to form a protective layer; the material of the shell layer is boron lithium compound; between the two particles of the core-shell structure oxide solid electrolyte powder, lithium ions migrate. Figure 1 The mark 13 in the figure indicates the path of lithium ion migration between particles.
[0052] The core-shell structured oxide solid electrolyte powder is preferably prepared by the aforementioned method for preparing the core-shell structured oxide solid electrolyte powder of the present invention.
[0053] The present invention also proposes an application of the aforementioned core-shell structure oxide solid electrolyte powder in the field of lithium electronic battery technology. The technical solution of the present invention improves the preparation process of the solid electrolyte powder, optimizes the grain boundary defect structure, and adjusts the surface components of the electrolyte to form a core-shell structure to improve its chemical stability and prevent the formation of an insulating layer, thereby improving the performance of lithium-ion batteries.
[0054] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0055] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0056] Embodiment 1:
[0057] This embodiment prepares a lithium lanthanum zirconium oxide (LLZO) electrolyte powder with a LiBO2 protective layer on the surface, and the specific operation steps are as follows:
[0058] 1) Preparation of lithium lanthanum zirconium oxide (LLZO) electrolyte powder by coprecipitation method
[0059] Weigh 483 g of lithium nitrate (LiNO3), 975 g of lanthanum nitrate (La(NO3)3), and 678 g of zirconium nitrate (Zr(NO3)4), add them to 2 L of water, and stir magnetically for 10 minutes to dissolve all the solids to obtain a salt solution.
[0060] 2) Use a burette to drop a 10% ammonia solution into the salt solution prepared in this example to produce a precipitate. When the amount of the precipitate produced by visual observation no longer increases, stop dropping the ammonia solution. At this time, place the obtained precipitate on filter paper for vacuum filtration. Add ethanol to the vacuum filtered filter cake and wash it three times, and filter it; add 4L of ethanol to it, place it on a stirrer for magnetic stirring for 30 minutes, and obtain a first suspension.
[0061] 3) The first suspension prepared in this example is poured into the discharge barrel of a high-speed homogenizer, and is homogenized and crushed at a flow rate of 1500 m / s and a pressure of 1000 bar to form a suspension of oxide electrolyte powder, i.e., the second suspension.
[0062] 4) Add 70 g of lithium metaborate (LiBO2) powder to the second suspension prepared in this embodiment, pour the mixture into the discharge barrel of a high-speed homogenizer, and homogenize and crush it at a flow rate of 1500 m / s and a pressure of 1000 bar to make it into a suspension of oxide electrolyte powder, that is, the third suspension.
[0063] 5) The third suspension prepared in this embodiment is vacuum dried at 80°C; the obtained powder is cold isostatically pressed into a green body; the green body is placed in a tubular furnace, and heated at a calcination temperature of 400°C for 1 hour in a nitrogen atmosphere to obtain a core-shell structured oxide solid electrolyte powder.
[0064] Embodiment 2:
[0065] Compared with Example 1, in step 4) of Example 2, 320.4 g of lithium metaborate (LiBO2) powder was added.
[0066] Embodiment 3:
[0067] Compared with Example 1, in step 4) of Example 3, 2.136 g of lithium metaborate (LiBO2) powder was added.
[0068] Embodiment 4:
[0069] Compared with Example 1, in step 4) of Example 4, after the step of adding lithium salt to the second suspension for second pressurized homogenization and crushing, the step further includes: adding lithium salt to the suspension after the second pressurized homogenization and crushing, and performing the second pressurized homogenization and crushing again.
[0070] Embodiment 5:
[0071] Compared with Example 1, in step 5) of Example 5, the calcined product is subjected to a second sintering; the temperature of the second sintering is 800°C.
[0072] Example 6
[0073] Compared with Example 5, in step 5) of Example 6, the temperature of the second sintering is 1050°C.
[0074] Embodiment 7:
[0075] Compared with Example 5, in step 5) of Example 7, the temperature of the second sintering is 900°C.
[0076] Example 8
[0077] Compared with Example 1, in step 4) of Example 6, after the step of adding lithium salt to the second suspension for second pressurized homogenization crushing, the step further includes: adding lithium salt to the suspension after the second pressurized homogenization crushing, and again performing second pressurized homogenization crushing; in step 5), the calcined product is subjected to a second sintering; the temperature of the second sintering is 800°C.
[0078] Embodiment 9:
[0079] Compared with Example 8, in step 2) of Example 9, the mass concentration of ammonia water is 0.01%; in step 3), the first suspension is homogenized and crushed at a flow rate of 1500 m / s and a pressure of 1500 bar; in step 4), the second suspension is homogenized and crushed at a flow rate of 500 m / s and a pressure of 1500 bar; in step 5), the sintering temperature is 200°C, the sintering time is 0.5h, and the sintering atmosphere is argon; in step 5), the sintering is hot isostatic pressing; the sintering also includes a second sintering after the sintering; the temperature of the second sintering is 800°C.
[0080] Embodiment 10:
[0081] Compared with Example 8, in step 2) of Example 10, the concentration of ammonia water is 5%; in step 3), the first suspension is homogenized and crushed at a flow rate of 2000 m / s and a pressure of 1200 bar; in step 4), the second suspension is homogenized and crushed at a flow rate of 2000 m / s and a pressure of 1300 bar; in step 5), the sintering temperature is 500°C, the sintering time is 5h, and the sintering atmosphere is helium; the sintering in step 5) also includes a second sintering after the sintering; the temperature of the second sintering is 1050°C.
[0082] Comparative Example 1:
[0083] Same as Example 1, except that lithium metaborate (LiBO2) powder is not added in step 4).
[0084] Comparative Example 2:
[0085] Same as Example 1, except that in step 4), the amount of lithium metaborate (LiBO2) powder added is 1.27 g.
[0086] Comparative Example 3:
[0087] Same as Example 1, except that in step 4), the amount of lithium metaborate (LiBO2) powder added is 370.45 g.
[0088] Comparative Example 4
[0089] Compared with Example 1, the difference is that in Comparative Example 4, lithium salt is added, but the second pressurized homogenization and crushing is not performed.
[0090] Comparative Example 5
[0091] Compared with Example 1, the difference is that in Comparative Example 5, lithium salt is added but no coating operation is performed, and lithium salt is only added during the preparation of electrolyte powder.
[0092] The electrolyte powders prepared in Examples 1 to 10 and Comparative Examples 1 to 5 were made into electrolyte sheets, and then the ion conductivity test, rate performance test and cycle rate performance test were carried out.
[0093] Ionic conductivity test methods include:
[0094] The ionic conductivity of the solid electrolyte is obtained by assembling a blocking electrode and performing an electrochemical impedance spectroscopy (EIS) test. The specific operation method is as follows:
[0095] The prepared composite oxide solid electrolyte sheet was used with stainless steel sheets as blocking electrodes on both sides to form a symmetrical battery. The electrochemical workstation used was DH7001 with a frequency range of 0.01 to 106 Hz, test the EIS of oxide solid electrolyte sheets at 25°C. The ionic conductivity of the solid electrolyte is calculated as follows:
[0096] δ=L / (R·S)
[0097] Where, δ is the ionic conductivity (unit S / cm), L is the thickness of the solid electrolyte sheet (unit cm), R is the intrinsic resistance of the solid electrolyte (unit Ω), S is the effective cross-sectional area of the solid electrolyte sheet (unit cm 2 ). The higher the test result of ionic conductivity, the better its ionic conductivity.
[0098] The test results are as follows:
[0099] Table 1 Ionic conductivity test results of various embodiments and comparative examples
[0100] Group Ionic conductivity (S / cm) Example 1 <![CDATA[10.31×10 -4 ]]> Example 2 <![CDATA[15.91×10 -4 ]]> Example 3 <![CDATA[8.53×10 -4 ]]> Example 4 <![CDATA[11.64×10 -4 ]]> Example 5 <![CDATA[11.64×10 -4 ]]> Example 6 <![CDATA[11.65×10 -4 ]]> Example 7 <![CDATA[11.63×10 -4 ]]> Example 8 <![CDATA[13.84×10 -4 ]]> Example 9 <![CDATA[13.64×10 -4 ]]> Example 10 <![CDATA[13.86×10 -4 ]]> Comparative Example 1 <![CDATA[3.84×10 -4 ]]> Comparative Example 2 <![CDATA[4.75×10 -4 ]]> Comparative Example 3 <![CDATA[15.95×10 -4 ]]> Comparative Example 4 <![CDATA[9.54×10 -4 ]]> Comparative Example 5 <![CDATA[6.87×10 -4 ]]>
[0101] The test methods for rate performance include:
[0102] Make a solid-state battery with lithium cobalt oxide as the positive electrode and metallic lithium as the negative electrode to evaluate the rate performance of the oxide solid electrolyte. The specific operation method is as follows:
[0103] Lithium cobalt oxide, conductive agent Super P, and binder PVDF (polyvinylidene fluoride) were mixed in a mass ratio of 9:0.5:0.5, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added and stirred to prepare a positive electrode slurry, which was coated on aluminum foil, dried at 100°C, and then cut into discs with a diameter of 10 mm as positive electrodes. CR2032 button batteries were assembled in the order of positive electrode sheet-composite oxide solid electrolyte sheet-lithium foil. Battery rate test was performed.
[0104] The operating voltage range of the all-solid-state lithium secondary battery is set to 3V to 4.2V, and the current density is 0.15 mA / cm 2 ) at a constant current to 4.2 V, and then at a constant voltage to 0.01C cutoff; then discharged to 3 V at currents of 0.1C, 0.2C, 0.5C, and 1C, respectively, to obtain the gram capacity of the material at 0.1C, 0.2C, 0.5C, and 1C discharge rates, respectively.
[0105] The test results are as follows:
[0106] Table 2 Rate performance test results of each embodiment and comparative example
[0107]
[0108] The methods for cyclic performance testing include:
[0109] Assemble CR2032 button cells according to the rate performance test method. 2 ) at a constant current of 4.2 V, and then at a constant voltage of 0.05 C for cut-off. Each cycle was repeated for 100 times, and the capacity retention rate was calculated.
[0110] The test results are as follows:
[0111] Table 3 Cyclic performance test results of various embodiments and comparative examples
[0112] 50 cycle capacity retention rate (%) 100 cycle capacity retention rate (%) Example 1 97.2 94.6 Example 2 99.1 96.4 Example 3 95.8 93.4 Example 4 98.4 96.1 Example 5 98.5 96.2 Example 6 98.8 96.6 Example 7 98.4 96.1 Example 8 98.9 96.8 Example 9 98.6 96.3 Example 10 98.6 96.3 Comparative Example 1 93.5 90.9 Comparative Example 2 94.2 91.7 Comparative Example 3 99.1 96.4 Comparative Example 4 96.7 93.4 Comparative Example 5 95.6 92.4
[0113] Based on the experimental data measured in Tables 1 to 3, it can be known that in the preparation method of Example 1, by introducing lithium salt and constructing a core-shell structure, the electrical properties of the product can be significantly improved. The core of achieving this effect is that in the core-shell structure, the lithium salt acts as a protective layer, which can effectively prevent the lithium-containing oxide in the oxide electrolyte from chemically reacting with water and carbon dioxide in the air to produce an insulating layer to cause grain boundary impedance, thereby improving the stability of the oxide electrolyte. At the same time, the protective layer can also curb the loss of lithium ions in the oxide electrolyte during the later sintering process, thereby improving its electrical properties.
[0114] In contrast, Comparative Examples 1 and 2 have lower electrical properties due to no or small amounts of lithium salt added. Although Comparative Example 3 adds more than 15% of lithium salt, it only achieves electrical properties similar to those of Example 2. However, considering the high cost of lithium salt, Example 2 has a greater advantage in cost-effectiveness.
[0115] Further analysis shows that Example 4 ensures that the lithium salt is completely coated on the surface of the oxide electrolyte particles through three times of pressurization and homogenization crushing. This fine treatment can greatly enhance the improvement effect of lithium salt on the electrical properties of the oxide electrolyte, thereby improving the electrical properties of the product.
[0116] In addition, a second sintering step was introduced in Examples 5 to 7. Compared with Example 1 which did not adopt this step, the performance of the products obtained in Examples 5 to 7 was better. It can be seen that the second sintering process plays a key role in significantly improving the density of the finished oxide electrolyte, thereby optimizing the electrical properties of the product.
[0117] Comparative Example 4 only performs the first pressurization homogenization, and fails to fully achieve the coating effect of the lithium salt, resulting in poor electrical properties of its product, which is lower than that of Example 1. This can explain that in Example 1, the first pressurization homogenization is performed first to control the particle size of the oxide electrolyte to be finer and more uniform; and then the second pressurization homogenization is performed to completely coat the surface of the oxide electrolyte particles with the lithium salt, thereby improving the improvement effect of the lithium salt on the electrical properties of the oxide electrolyte.
[0118] Finally, although lithium salt is also added in Comparative Example 5, it is only a simple doping treatment and fails to achieve full coverage of the surface of the oxide electrolyte particles by lithium salt as in Example 1. Therefore, the improvement of its electrical properties is limited and far lower than that in Example 1. In Example 1, two pressurization homogenizations are used, which enables the lithium salt to completely cover the surface of the oxide electrolyte particles, thereby improving the improvement effect of the lithium salt on the electrical properties of the oxide electrolyte.
[0119] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0120] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a core-shell structured oxide solid electrolyte powder, characterized in that: It includes the following steps: 1) preparing an electrolyte raw material into a first suspension; 2) subjecting the first suspension to a first pressurized homogenization and crushing process to obtain a second suspension; 3) adding lithium salt to the second suspension to perform a second pressurized homogenization and crushing to obtain a third suspension; 4) The third suspension is filtered, dried, and sintered in an inert or neutral atmosphere to obtain a core-shell structured oxide solid electrolyte powder.
2. The preparation method according to claim 1, characterized in that: The particle size of the electrolyte raw material is 0.1 to 500 μm.
3. The preparation method according to claim 1, characterized in that: The flow rate of the first pressurized homogenization crushing and the second pressurized homogenization crushing is 500-2000 m / s, and the pressure is 1000-1500 bar; the temperature of the second suspension and the third suspension is ≤120°C, and the viscosity is ≤2000cp.
4. The preparation method according to claim 1, characterized in that: The lithium salt is a boron lithium compound, which is selected from at least one of LiBH4, LiBF4, Li2B4O7, Li3BO3 and LiBO2; based on the mass of the electrolyte raw material, the addition amount of the lithium salt is 0.1-15%.
5. The preparation method according to claim 1, characterized in that: After the step of adding lithium salt to the second suspension for second pressurized homogenization and crushing, the method further includes: adding lithium salt to the suspension after the second pressurized homogenization and crushing, and performing the second pressurized homogenization and crushing again; the step of adding lithium salt to the suspension after the second pressurized homogenization and crushing, and performing the second pressurized homogenization and crushing again is performed n times, where n is a natural number.
6. The preparation method according to claim 1, characterized in that: The step of preparing the electrolyte raw material into a first suspension is as follows: 1a) dissolving a soluble salt in a first solvent to obtain a salt solution; the soluble salt is selected from at least one of nitrates, sulfates, halides, hydroxides and carbonates; the first solvent is selected from any one of water, acetonitrile, anhydrous ethanol, methanol, tetrahydrofuran, dimethylformamide and dimethyl sulfoxide; 1b) adding ammonia water dropwise to the salt solution to form a precipitate; the mass concentration of the ammonia water is 0.01-10%; 1c) filtering the precipitate, adding a second solvent thereto, stirring, and obtaining a first suspension; the second solvent is selected from any one of water, anhydrous ethanol, methanol and dimethylformamide.
7. The preparation method according to claim 1, characterized in that: The sintering temperature is 200-500° C., the sintering time is 0.5-5 hours, and the sintering atmosphere is air, nitrogen, argon or helium.
8. The preparation method according to claim 7, characterized in that: The sintering is cold isostatic pressing sintering or hot isostatic pressing sintering; or, the sintering further includes a second sintering; the temperature of the second sintering is 800-1050°C.
9. A core-shell structure oxide solid electrolyte powder, characterized in that: The particles constituting the core-shell structured oxide solid electrolyte powder include: The core is a solid particle made of an oxide electrolyte; The shell layer is coated on the surface of the solid particles; the material of the shell layer is boron lithium compound.
10. Use of the core-shell structure oxide solid electrolyte powder according to claim 9 in the field of lithium electronic battery technology.